Report on the “Advanced Big Data Training School for Life Sciences”, Barcelona 3th-7th September 2018 - Hoang, Yen; Pfeil, Juliane; Zagorščak, Maja; Thieffry, Axel YA; Zdravevski, Eftim; Ramšak, Živa; Lameski, Petre; K Schulze, Sabrina; Papakonstantinou, Eleni; Papageorgiou, Louis; Singh, Tarry; Duarte-López, Ariel; et al. (My University, 2018)
The “Advanced Big Data Training School for Life Sciences” took place during September 3-7, 2018, organized by the Data Management Group (DAMA-UPC) at the Technical University of Catalonia (UPC) in Barcelona, Spain. It is the follow-up training school of the first “Big Data Training School for Life Sciences”, held in Uppsala, Sweden, in September 2017, which was defined and structured at the “Think Tank Hackathon”, held in Ljubljana, Slovenia, in February 2018. The aim of this training school was to get participants acquainted with emerging Big Data processing techniques in the field of Computational Biology and Bioinformatics.